Publishing online - Jalbuena, Oscar Samuel Johnson
This study proposes a course outline for Internet of online publishing as a subject under the journalism curriculum of College of Mass Communication at the University of the Philippines at Diliman (CMC-UP). The study investigated what is available for publishers on the Internet, as well as what is meant by "online publishing." Specifically, a historical survey of the development and evolution of the Internet as a publishing and communications vehicle is explored. Two primary research studies were conducted; one, to create the course outline on Internet publishing; and, the other, to determine opinions concerning such a special topic as part of curriculum. The study used action research as a study design to provide change and understanding in situations in which it was too difficult to control variables. The action research methodology also provided rigor through the spiral of its cyclic and dialectic processes.